Energetic consequences and implications for food consumption models when feeding on various sizes of cod in harp seals (Phoca groenlandica) - Algera, Ann-Isabel (UiT Norges arktiske universitet, 2016)
The current population-based food consumption models assume that harp seals are swallowing fish whole. However, behaviours such as belly-biting and rejection of fishes’ heads has been observed, possibly biasing diet analysis based on hard parts such as otoliths, and consequently underestimating the total food consumption of fish by harp seals. The purpose of this study was to examine whether individual fish are in fact being consumed in their entirety or if behaviours such as belly-biting and rejection of fish heads - where the seal actively seeks out the most energy rich part of its prey - is occurring under certain circumstances. Two female harp seals, maintained in human care, were fed live cod and saithe ranging from 90 g – 2710 g and 20 cm – 70 cm. The caloric energy content of the discarded piece(s) was quantified, estimating the energy wastage by the seals when they consume different sizes of prey. Fish that were too large to swallow were consequently torn into pieces before ingested. The adult harp seal was unable (or did not choose) to swallow whole those fish weighing above 750 g, whereas the juvenile showed the same trend at 380 g. Fish parts frequently rejected included the head, the head with parts of the back attached, and all but the abdomen of the fish. 81 % of the remains left by the adult contained otoliths, while this number was a staggering 100 % for the juvenile. 1 % to 40 % of the caloric content in the fish was wasted depending on the fish body mass, i.e. a larger body mass yielded a larger caloric wastage. Undigested fish parts were collected on seven occasions in the tanks, suggesting that regurgitation might be frequent when seals are feeding on bony fish species. The findings from this study indicate that harp seals may seek out the most energy-rich parts of a fish, subsequently leaving “lower-energy” remains behind, and that this “waste” of energy increases with the mass of its prey. As such, reassessment of the current estimations of food consumption may be valuable in terms of ...